(untitled) (Fiep Bulletin - online, 2016)
Objective: Identify the comorbidities of the chronic renal patients and research the main complications manifested during the hemodialysis treatment. Method: cross-sectional epidemiological research, carried out at the Santo Amaro Nephrological Clinic, in the municipality of Patos-PB with individuals in hemodialysis, in the months of September to October 2011. The analysis occurred through descriptive statics. Results: 51,7% of the participants were men, 81% in the age group between 18 to 59 year-olds. In relation to the comorbidities of the CRI were identified arterial hypertension (34,5%), diabetes mellitus (13,8%), cardiac insufficiency (10,3%) and myocardial infarction (6,9%) and visual impairment (6,9%). The main complications were: cramps (65,5%), weakness (50%), arterial hypertension during dialysis (48,3%), headache (48,3%) and weight loss (44,8%). Conclusion: many are the comorbidities associated to the chronic renal patient; however, arterial hypertension and the diabetes mellitus are highlighted, and should be considered in the health care.